The pragmatics of dialogical asides in Shakespeare - Mullini, Roberta (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2017)
All modern editions of Shakespeare plays signal the theatrical convention of the aside to actors and readers by adding precise stage directions, and scholars have defined various categories for this phenomenon. Among these categories (monological, ad spectatores, and dialogical) this article examines the dialogical aside and the pragmatic strategies it involves, when dialogue becomes hidden, so as not to be discovered by other onstage bystanders. In other words, a dialogical aside operates when a character in a multiparty talk chooses only one or more characters as their addressee, thus creating a dialogically privileged group and excluding the remaining bystanders. The article starts investigating quantitative data deriving from a search via a concordance software and devotes specific attention to the occurrences of this stage direction in The Tempest, Henry VI, Part 3 and Antony and Cleopatra, i.e. the plays that rank highest in the data. Keywords: Shakespeare, dialogical aside, pragmatic analysis, pragmatic strategies, The Tempest, Henry VI, Part 3, Antony and Cleopatra